Boosting Local Economy through Tourism: Community-Based Tourism on Cultural Tourism Activities - Prayoga, Tasya Zahwa; Rahmiati, Filda; Amin, Grace; Goenadhi, Felix; Hariri, Mohammed (Ilomata International Journal of Social Science, 2024)
Tourism may have a variety of positive outcomes including increased local economy, creation of jobs, and infrastructural improvements. The objective of this research is to examine the Community-based tourism (CBT) approach in order to achieve several SDGs to strengthen local economy. This study employs a qualitative approach that includes observation and interviews conducted in phases with Kutu Wetan Village, Indonesia. The village has the competitive advantage of having several cultural attractions with rich history story about the presence of Ponorogo regency. All of the measures in this study are used with the intention of stimulating the development of all tourism facilities to increase the destination’s appeal that diversifying the local economy and creating jobs. Results shows that Kutu Wetan Village still lack variety of entrance points (tour packages, cultural events, homestays, culinary option, and transportation business). Successful implementation of CBT Kutu Wetan are depends on their cooperative mindset and local’s strong economic interest. To achieve long-term sustainable tourism development in supporting the local economy, it is important for Kutu Wetan village to build an appealing and genuine destination that offers diversify tourist attraction while maintaining the surrounding environment and culture.